Pengaruh Komitmen Organisasi dan Budaya Kerja Islami Terhadap Prestasi Kerja Karyawan Pada KSPPS BMT Aman Utama Jepara - Amru Nawawi; Silviana Pebruary (Jurnal Rekognisi Akuntansi, 2019)
This research aims to analyze the influence of organizational commitment and Islamic work culture on employee work performance on KSPPS BMT Aman Utama Jepara partially. To analyze the influence of organizational commitment and Islamic work culture on employee work performance on KSPPS BMT Aman Utama Jepara simultaneously. To analyze which factors most affect employee work performance at KSPPS BMT Aman Utama Jepara. The population in this study was employees of KSPPS BMT Aman Utama Jepara which amounted to 48 people. The data analysis techniques used are multiple linear regression, t test and F test. The results showed that there was an influence on organizational commitment to employee work performance in KSPPS BMT Aman Utama Jepara. There is an influence of Islamic work culture on employee work performance on KSPPS BMT Aman Utama Jepara. There is an influence of organizational commitment and simultaneous Islamic work culture on employee work performance at KSPPS BMT Aman Utama Jepara. Based on the regression value, the factor that has the most influence on employee work performance is organizational commitment. So it is expected that KSPPS BMT Aman Utama Jepara to increase employee commitment so that work performance increases.